Factors That Influence Orange Farmers Using Mixed Cropping Pattern in Nagori Bandar Purba, Purba District, Simalungun Regency - Wahyunita Sitinjak (Postgraduate, University of Mataram, 2025)
The problems studied in this study are (1) How much additional income does orange farmers get by using intercropping planting patterns in the research area? (2) What are the business risks that occur in orange intercropping farming in Pura Subdistrict, Simalungun Regency? This study aims to determine what factors make farmers use orange intercropping planting patterns in Bandar Pura Village, Pura Subdistrict, Simalungun Regency. The data used are primary data obtained from intercropping orange farmers with a sample of 30 respondents, secondary data obtained from relevant agencies. The results of the study show that orange production of 15,882 kg received an income of Rp. 190,059,200 with a production cost of Rp. 83,170,162 with an income of Rp. 106,349,683, the feasibility of orange farming with intercropping planting patterns can be calculated by R/C analysis. Based on the research results, the R/C value was 2.23, meaning that each R/C result was 2.0 > 1, indicating that orange farming in Bandar Purba Village, Purba District, Simalungun Regency was profitable and worth developing.